Elderly Empowerment Through The Activities Of Brain Function Cognitive Stimulation Elderly In Mersi Village District Banyumas - Kuswati, Ani; Sumedi, Taat; Wahyudi, Wahyudi (Journal of Bionursing, 2019)
Background. The decline of cognitive function in the elderly is the biggest cause of the inability to perform normal daily activities and is also the most common reasons that lead to dependence on others to care for themselves. Various scientific-based studies have shown a variety of the fact that many can be done ways to slow the aging process of the brain. This brain stimulation activities include physical activity, mental stimulation and social activities.Objective. to determine the effect of empowering the elderly through brain stimulation on cognitive function in the elderly. Method: This study used a pre-experimental design to form one group pretest-posttest design, the number of respondents 46 people elderly. The statistical test used was Wilcoxon Signed Test Runs.Results. The results of this study are the effect of empowering the elderly through brain stimulation on cognitive function in the elderly (p = 0.001).Conclusion. The activities of brain stimulation in the elderly in an integrated group which includes physical activities, spiritual activities and social activities affect the risk of cognitive decline.